No substantial gender differences in suspected adverse reactions to ACE inhibitors and ARBs: results from spontaneous reporting system in Campania Region. (1st December 2016) - Sportiello, Liberata; Rafaniello, Concetta; Sullo, Maria Giuseppa; Nica, Mihaela; Scavone, Cristina; Bernardi, Francesca Futura; Colombo, Delia Maria; Rossi, Francesco
ABSTRACT: Background : Today, there is a poor knowledge about gender differences in adverse drug reactions (ADRs) to cardiovascular drugs such as angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs). Therefore, the aim of this study was to analyze spontaneous reports of suspected ADRs induced by ACE-inhibitors and ARBs, between January 2001 and June 2015, recorded in a Region of Southern Italy (Campania Region). Methods : We performed a descriptive gender-related analysis of regional safety data, obtained from the spontaneous reporting system. Results : In the considered period, 772 suspected ADRs to ACE inhibitors and ARBs (in monotherapy or in combination) were reported with a slightly higher frequency in men compared with women. In both genders, the most involved category was ARBs in combination, whereas the most prescribed active substance was ramipril. General and administration site conditions, vascular disorders and modification of laboratory parameters were more common in men, while respiratory disorders were most common in women. In 88.2% of cases, not serious ADRs were described more by men than women. Conclusions : This analysis suggested no substantial gender differences. Further studies such as randomized population studies or meta-analysis of ACE inhibitors and ARBs randomized studies are needed to clarify whether gender differences exist in the safety profile of these drugs.